ENRICHING STUDENTS SPEAKING’S SKILL THROUGH SONG - Ruung, Joshua; Liando, Nihta; Rorimpandey, Rinny (Program Studi Pendidikan Bahasa Inggris, 2024)
Songs are an excellent 'tool' to help the learning process students' English, more specifically songs are believed to be able to motivate students while studying English. Speaking as the one of four basic skills nowadays become more challenging for the students, but in the contrary there are so many students lack of speaking ability. The purpose of the study is to enriching students speaking’s skill through song. Using The design that will apply in this research was pre-experimental design with one group pre-test and post-test class action research, this study employs a quantitative descriptive analytic technique. The number of samples in this study were 8 grade XI students of SMA Yadika Langowan who had been involved in the use of songs to enriching students speaking’s skill. The results showed that the eleven students of SMA Yadika Langowan had a higher score, especially to improve the speaking ability. Therefore, it is hoped that songs can also help to develop Pronunciation Skills with good intonation. Children will prefer English quickly because this way of learning will create a fun atmosphere and not feel bored.